Implementation of Islamic Economic Principles In The Employee Reward System At BMT Marhamah Purworejo - Heny Rahmawati; Imam Turmudi; Siti Chasanah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2026)
Essentially, the workplace requires human resources with a strong work ethic and high motivation to drive increased productivity and demonstrate commitment to achieving established goals. To foster and maintain consistent and even increasing work enthusiasm, one important aspect that needs to be considered is the implementation of a reward system. This study aims to determine the application of rewards to employee productivity at BMT Marhamah. This study uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation. Secondary data sources were obtained from the results of a library study through literature supporting this research. The results show that BMT Marhamah Purworejo in implementing a reward system has integrated modern management principles with Islamic values. However, its effectiveness is still not optimal due to issues of consistency, transparency, and objectivity. Simultaneously, the reward system implemented at BMT Marhamah Purworejo has proven ineffective in encouraging employee productivity, discipline, and work quality.